Isolation and characterization of 9-lipoxygenase and epoxide hydrolase 2 genes: insight into lactone biosynthesis in mango fruit (Mangifera indica L.) - Deshpande, Ashish B.; Chidley, Hemangi G.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Phytochemistry, 2017)
Uniqueness and diversity of mango flavour across various cultivars are well known. Among various flavour metabolites lactones form an important class of aroma volatiles in certain mango varieties due to their ripening specific appearance and lower odour detection threshold. In spite of their biological and biochemical importance, lactone biosynthetic pathway in plants remains elusive. Present study encompasses quantitative real-time analysis of 9-lipoxygenase (Mi9LOX), epoxide hydrolase 2 (MiEH2), peroxygenase, hydroperoxide lyase and acyl-CoA-oxidase genes during various developmental and ripening stages in fruit of Alphonso, Paid and Kent cultivars with high, low and no lactone content and explains their variable lactone content. Study also covers isolation, recombinant protein characterization and transient over-expression of Mi9LOX and MiEH2 genes in mango fruits. Recombinant Mi9LOX utilized linoleic and linolenic acids, while MiEH2 utilized aromatic and fatty acid epoxides as their respective substrates depicting their role in fatty acid metabolism. Significant increase in concentration of delta-valerolactone and gamma-decalactone upon Mi9LOX over-expression and that of delta-valerolactone, gamma-hexalactone and delta-hexalactone upon MiEH2 over-expression further suggested probable involvement of these genes in lactone biosynthesis in mango. (C) 2017 Elsevier Ltd. All rights reserved.